2011
DOI: 10.1175/2011jcli3983.1
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Inter–El Niño Variability on the Tropical Atlantic and Northeast Brazil Climate

Abstract: In this study, observations and numerical simulations are used to investigate how different El Niño events affect the development of SST anomalies in the Atlantic and how this relates to the Brazilian northeast (NE) precipitation. The results show that different types of El Niño have different impacts on the SST anomalies of the equatorial and tropical South Atlantic but a similar SST response in the tropical North Atlantic. Strong and long (weak and short) El Niños with the main heating source located in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
126
2
21

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(160 citation statements)
references
References 56 publications
11
126
2
21
Order By: Relevance
“…Following the former argument, Lübbecke and McPhaden (2012) have discussed the different equatorial Atlantic responses from ENSO forcing and they have pointed out the conditions over the NTA as the responsible for a delayed feedback through Rossby wave propagation. De Almeida and Nobre (2012) have suggested from observations how ENSO weaken the equatorial Atlantic variability while Rodrigues et al (2011) have confirmed the different impacts of Pacific El Niño-types over the Equatorial Atlantic.…”
Section: Introductionmentioning
confidence: 94%
“…Following the former argument, Lübbecke and McPhaden (2012) have discussed the different equatorial Atlantic responses from ENSO forcing and they have pointed out the conditions over the NTA as the responsible for a delayed feedback through Rossby wave propagation. De Almeida and Nobre (2012) have suggested from observations how ENSO weaken the equatorial Atlantic variability while Rodrigues et al (2011) have confirmed the different impacts of Pacific El Niño-types over the Equatorial Atlantic.…”
Section: Introductionmentioning
confidence: 94%
“…This is mainly due to the dependence of its rainy season upon oceanic and atmospheric conditions in the tropical Pacific and Atlantic Oceans. Previous studies using dynamic and statistical modeling have demonstrated that the relationship between oceanic and atmospheric conditions in the equatorial Pacific and tropical Atlantic and the seasonal rainfall over the northern part of the Brazilian Northeast allows large climate events to be forecasted with a lead time of a few months (Hastenrath 1990, Hastenrath and Greischar 1993, Marengo et al 2013, b, Giannini et al 2004, Nobre et al 2006, Rodrigues and McPhaden 2014, Rodrigues et al 2011, Hounsou-Gbo et al 2016, among others).…”
Section: Introductionmentioning
confidence: 99%
“…Not all El Niño phases result in a drought in NEB, however [Kane, 1997;Erasmi et al, 2009]. Recently, Rodrigues et al [2011] showed that the inter-El Niño variability has to be taken into account, when accessing the effects of El Niño phases on precipitation in NEB. The authors highlighted that strong and long (weak and short) El Niño phases lead to dry (wet) conditions in NEB.…”
mentioning
confidence: 99%